Heritage and the sacred: introduction - Meyer, Birgit (Material religion, 2013)
Heritage formation involves some kind of sacralization, through which cultural forms are lifted up and set apart. But success is not guaranteed in the making of heritage, and the cultural forms that are singled out may well fail to persuade. Heritage formation is a complicated, contested politicalaesthetic process that requires detailed scholarly explorations and comparative analysis. Which aesthetic practices are involved in profiling cultural forms as heritage? What are the politics of authentication that underpin the selection and framing of particular cultural forms? To which contestations does the sacralization of particular cultural formsin particular, those derived from the sphere of religiongive rise? Which aesthetics of persuasion are invoked to render heritage sacred for its beholders? Calling attention to various facets of the relation between heritage and the sacred, this special issue offers detailed explorations of how form, style, and appearance seek to vest selected objects and performative practices with sacrality.